A Large Magnetoresistance Effect in p–n Junction Devices by the Space‐Charge Effect. (6th February 2013) - Yang, Dezheng; Wang, Fangcong; Ren, Yang; Zuo, Yalu; Peng, Yong; Zhou, Shiming; Xue, Desheng
Abstract The finding of an extremely large magnetoresistance effect on silicon based p–n junction with vertical geometry over a wide range of temperatures and magnetic fields is reported. A 2500% magnetoresistance ratio of the Si p–n junction is observed at room temperature with a magnetic field of 5 T and the applied bias voltage of only 6 V, while a magnetoresistance ratio of 25 000% is achieved at 100 K. The current‐voltage (I–V) behaviors under various external magnetic fields obey an exponential relationship, and the magnetoresistance effect is significantly enhanced by both contributions of the electric field inhomogeneity and carrier concentrations variation. Theoretical analysis using classical p–n junction transport equation is adapted to describe the I–V curves of the p–n junction at different magnetic fields and reveals that the large magnetoresistance effect origins from a change of space‐charge region in the p–n junction induced by external magnetic field. The results indicate that the conventional p–n junction is proposed to be used as a multifunctional material based on the interplay between electronic and magnetic response, which is significant for future magneto‐electronics in the semiconductor industry.